The effect of different rate of oil palm wastes compost towards soil physical properties / Muhammad Syarifuddin Sukri - Sukri, Muhammad Syarifuddin (Faculty of Plantation and Agrotechnology, 2019)
Water is essential element that plant as water need water to convert light to energy by photosynthesis process. Observation from common nursery shows that they have to apply more water than the requirement as medium cannot hold the water at optimum rate. This main research purpose is to study how different rate of oil palm wastes compost affect water holding capacity rate, bulk density and organic matter content. The research done by comparing three type of oil palm compost that are kernel shell, pressed palm fruits and empty fruit bunch mixed with nursery soil with 5 different ratios which are T1 (70% of compost), T2 (71% of compost), T3 (72% of compost), T4(73% of compost) and T5 (74% of compost). The data collected is on soil moisture by using gravimetric water content method that use weight to calculate the water content. The organic material (OM) value also calculated through gravimetric method and bulk density is measured by divide dried soil weight with soil volume. The oil palm seedling transplanted to polybag to ensure real field uncontrollable variable factors present. The result shows that types of wastes effect were all have significant difference effect toward the water content, OM and bulk density which all have P-Value equal to 0.00. Significant difference also shown at wastes ratios effect toward OM content with 0.004 P-Value. By doing this research, I hope that the results can be used in improving the nursery plant medium and for future studies.